Formulation and implementation, convergences and deviations: Facets of the Individual MicroEntrepreneur (MEI) public policy in the local plan - Campanha, Lucas Jose; De Lorenzo, Helena Carvalho; Fonseca, Sergio Azevedo [UNESP]; De Oriani E Paulillo, Luiz Fernando (FapUNIFESP (SciELO), 2017)
Public policies to support small enterprises have emerged in Brazil in the 2000s, having it as major milestones the Microenterprise and Small Size Business Statute, published in December 2006 via the complementary law n.123 and its successor, the Complementary Law 128 of December 2008, which became known as the Individual Micro Entrepreneur (MEI) Law (MEI's law). This paper addresses, as an object of study, the implementation process of the latter legal instrument in a spatiality defined by the municipality of Araraquara. The methodological strategy used was a qualitative research, outlined as a single case study of exploratory character, employing as instruments for data collection: both documental research as well as interviews with structured scripts. Results have shown that the dynamic imposed by the implementation of the law can be characterized by fragile inter-organizational ties and relations based on the maximization of individual interests, to the detriment of collective interests, which ought to be pursued by public policies. It was verified, on the analysis of the direct and indirect impacts and results, that the local government was not ready for the execution of the policy designed on the federal level. The agents in local level proceed in a manner to fragment the formalization into small bits, in which each one of them acts on its own environment, without interaction or complementation; as a consequence, the formalization process is carried out following a hierarchical order, which results in a segmented and fragmented implementation.
Keywords: Araraquara; Entrepreneurship; Microenterprise; Public agents